2016
DOI: 10.5152/balkanmedj.2016.16459
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Sexual Function, Psychological Status, and Sociodemographic Characteristics of Turkish Men within Polygamous and Monogamous Marriages

Abstract: Background: A limited number of studies within the literature have entailed objective evaluations of psychological, sexual, and emotional features of women within polygamous marriages. However, there is a lack of studies reporting these features among polygamous and monogamous men. Aims: The aim of this study was to investigate sociodemographic characteristics, sexual function, and psychological status of polygamously and monogamously married men. Study Design: Cross-sectional study. Methods: The study sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Another study conducted in north-central Nigeria also observed similar pattern where prevalence of depression was higher among women married in polygamous setting than in monogamous setting [20]. The lower prevalence observed in our study among those in polygamous marriages may not be unrelated to the fact that polygamous marriages are highest in the northwest region of Nigeria [21] (47.5%), thus making the women in this part of the country probably better adapted to marriages in polygamous settings than women in Turkey; moreover, polygamous marriage is illegal in Turkey [22], therefore, women who finds themselves in such relationship may likely be more prone to depression.…”
Section: Discussionmentioning
confidence: 60%
“…Another study conducted in north-central Nigeria also observed similar pattern where prevalence of depression was higher among women married in polygamous setting than in monogamous setting [20]. The lower prevalence observed in our study among those in polygamous marriages may not be unrelated to the fact that polygamous marriages are highest in the northwest region of Nigeria [21] (47.5%), thus making the women in this part of the country probably better adapted to marriages in polygamous settings than women in Turkey; moreover, polygamous marriage is illegal in Turkey [22], therefore, women who finds themselves in such relationship may likely be more prone to depression.…”
Section: Discussionmentioning
confidence: 60%
“…A union with the first wife which is characterized with some degree of discord may actually form the basis for marrying a second wife Ekerbicer et al. ( 2016 ). Sexual dissatisfaction in the first partnership is another reason for polygamous men to marry a second spouse Ekerbicer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dissatisfaction in the first partnership is another reason for polygamous men to marry a second spouse Ekerbicer et al. ( 2016 ) and might at the same time lead to a general feeling of discontent towards the first wife that can turn into physical aggression. In reverse, aggressive males could be more dissatisfied with their sexual activity and might look for a second wife more often than men with non-aggressive behavioral characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous research shows that polygamous marriages have negative effects, there are some studies that have found that polygamy has positive effects on families such as happiness (Thobejane & Flora, 2014), increasing the birth rate due to competition between spouses for childbirth because they believe their husbands love many children (Rossi, 2019) and reduce divorce (Gumani & Sodi, 2009;Khasawneh et al, 2011). In addition, a study conducted by Ekerbiçer et al (2016) found that polygamy was recognized to have a positive effect on men. Men who practice polygamy are less likely to suffer from depression than men who practice monogamy.…”
Section: Literature Reviewmentioning
confidence: 99%